2002
DOI: 10.1128/aac.46.8.2644-2647.2002
|View full text |Cite
|
Sign up to set email alerts
|

gyrA Polymorphism in Campylobacter jejuni : Detection of gyrA Mutations in 162 C. jejuni Isolates by Single-Strand Conformation Polymorphism and DNA Sequencing

Abstract: Mutations in the quinolone resistance-determining region of the gyrA gene from 138 ciprofloxacin-resistant (MIC, >4 g/ml) and 24 ciprofloxacin-susceptible (MIC, <1 g/ml) clinical Campylobacter jejuni isolates were subjected to single-strand conformation polymorphism analysis and sequencing. All of the isolates could be assigned to three genotypic clusters based on silent mutations. All resistant isolates had a point mutation at codon 86.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
44
6
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 27 publications
4
44
6
2
Order By: Relevance
“…BECKMANN et al (2004) reported the same silent mutations detected in this research, His-81-His and Ser-119-Ser, in quinolone sensitive strains. The silent mutation Ala-120-Ala, found in this study, was also previously described by WILSON et al (2000) and HAKANEN et al (2002).…”
Section: Discussionsupporting
confidence: 66%
“…BECKMANN et al (2004) reported the same silent mutations detected in this research, His-81-His and Ser-119-Ser, in quinolone sensitive strains. The silent mutation Ala-120-Ala, found in this study, was also previously described by WILSON et al (2000) and HAKANEN et al (2002).…”
Section: Discussionsupporting
confidence: 66%
“…These data, together with those recently published from Kuwait (Albert et al, 2005), show that, similar to other geographical locations (Zirnstein et al, 1999;Engberg et al, 2001;Hakanen et al, 2002;Dionisi et al, 2004;Beckmann et al, 2004), this mutation is the one most commonly encountered in fluoroquinolone-resistant isolates in the Middle East. Extensive polymorphism of the gyrA gene in C. jejuni within as well as outside the QRDR is well documented (Dionisi et al, 2004;Beckmann et al, 2004;Hakanen et al, 2002;Piddock et al, 2003). Based on partial sequences, the 35 fluoroquinolone-resistant strains encountered in this study carried 10 allelic variants of the gyrA gene (G1-G10), although distributed disproportionately (Fig.…”
mentioning
confidence: 74%
“…To investigate the molecular basis of high FQ resistance in the C. jejuni isolates, we analyzed the full gene sequences encoding the DNA gyrase subunits (gyrA and gyrB) (9,10) and the topoisomerase IV subunits (parC and parE) (11,12), which are known targets of FQ, the regulatory protein CmeR, and the sequence of the promoter region of cmeABC, which encodes an efflux pump (13,14), by DNA sequencing as previously described (15,16). The MICs of ciprofloxacin against the 39 isolates which represent different sequence variants were tested according to CLSI guidelines (17,28).…”
mentioning
confidence: 99%